The Difficulties of Learning English for the Beginner English Learners - Wiwiek Sundari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
English as an international language is used and learned by people not only from English speaking countries but also from non-English speaking countries. In Indonesia, English is a foreign language that has different pronunciation system with Indonesian language. Because of these differences, many beginner English learners meet with difficulties in learning English. In this library research, the researcher uses some references that carefully reviewed to gather data related to the information required for completing this article. It is found that beginner English learners usually face several obstacles in learning English, such as the difficulties in determining the word class of the same vocabulary, the difficulties in pronouncing due to different elements between English and Indonesian language, and also the difficulties because of the different distribution of phonetic characteristics between English and Indonesia.Keywords: pronunciation; learners; beginner; obstacles; characteristcs.